A new species of Neocypholaelaps Vitzthum (Acari: Ameroseiidae), with notes on the cheliceral lobes and ventral pore-like structures of mites of this family - Narita, João Paulo Z.; Pédelabat, Marie; de Moraes, Gilberto J. (Zootaxa, 2013)
Neocypholaelaps kreiteri n. sp. is described based on the morphology of adult females, males, deutonymphs, protonymphs and larvae collected on inflorescences of Cocos nucifera L. (Arecaceae) in La Réunion Island, Indian Ocean. This is the first species of Neocypholaelaps reported from that island. It is most similar to N. cocos Evans, 1963 and N. stridulans Evans, 1955. A discussion is presented about the presence of cheliceral lobes and the absence of pilus dentilis on the fixed cheliceral digit of ameroseiid species, relating that to what has been reported for the Melicharidae and the Phytoseiidae. A discussion is also presented about the identity of a pore-like structure positioned anteriad of the genital lyrifissures (iv5) in many ameroseiids. These are interpreted as being a pore that in many ameroseiids and in other Gamasina are often in-distinctly and located close to the posteromesad margin of coxae IV, on the posterior end of the exopodal shield.